The THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, CORE COMPETENCY, JOB SATISFACTION ON EMPLOYEE PERFORMANCE MEDIATED BY WORK ENVIRONMENT AT PT WINGS SURYA: Pengaruh Kepemimpinan Transformasional,Kompetensi Inti, Kepuasan Kerja Terhadap Kinerja Melalui Lingkungan Kerja Sebagai Mediasi Pada PT Wings Surya Surabaya - Lestari, Melati rahayu (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This study aims to determine the effect of transformational leadership, core competency and job satisfaction on employee performance meditated by work environment in PT Wings Surya Surabaya, with using four variable types. Independent variable is Core Competency (X1) and Transformational Leadership (X2). Dependent variable is Employee Performance (Y). Intervening Variable is Job Satisfaction (Z). Mediating Variable is Work Environment (M). This research used quantitative descriptive with primary data methods and online questionaries to collect data research with Likert scale. The analysis using WarPLS 7.0 to showed a significancy the variable to employee performance between work environment with SEM and PLS by testing data validity, reliability, hypothesis, and structural model. The respondent reacted that competency and leadership of manager can influence performance because the highly satisfaction, even work environment can’t moderated and created the accurated information. It’s important to the manager to upgrade the type of leadership, there for it can help the employee satisfaction and focusing on competency, so that it can develop the performance. The population is 277 employee and sampling using 74 employee with sampling methods judgement sampling in criteria six month minimum working period.